Particle dispersions in liquid media - Damm, Cornelia; Peukert, Wolfgang (Particle Separation Techniques, 2022)
Particle separation and characterization requires their individualization in dispersions at moderate concentrations. Powders must be properly wetted by the liquid while dispersion requires breaking particle-particle bonds. For aggregates forming solid bridges the bonds in the bridges and within the primary particles can be similar strong. Therefore, dispersion requires considerable stress energy input. Many different devices are available to disperse agglomerates (weak bonds) and aggregates (strong bonds) in the lab and at production scale. Their understanding and design is discussed from a unified perspective. The dispersed particles must be sufficiently stable against coagulation. Colloidal stability can be estimated by the Derjaguin, Landau, Verwey, and Overbeek theory and determined experimentally by analytical centrifugation. Finally, case studies are presented: solvent-mediated size-selective precipitation of quantum dots <10 nm, dispersion of novel 2D materials at moderate energy input and of organic pigments <1 μm, drugs, and particles from gas phase synthesis in high energy mills are discussed.<br